Consistency of Condom Use in the Prevention of HIV / AIDS At Risk Group Truck Drivers In Blora - Suharto Suharto; Erni Nuryanti; Sutarmi Sutarmi (Jurnal Riset Kesehatan, 2013)
This research analyzes many factors that influence the behavior so that can prevent HIV/AIDS by using condom consistently in group of truck driver who usually stay for awhile in the truck stop area. Descriptive co relational used in this research, with the cross sectional approach. Total technique sampling is used to recruit 50 samples. Data has been collected using a questioner and been analyzed using a chi square test. The result of this study reveals there is a relationship between a knowledge (p = 0,001), perception (p=0,001), condom availability (p=0,001) and role of health services (p=0,001) with the behavior of preventing HIV/AIDS. Based on logistic regression test, the most influence factor in using condom consistently is knowledge.